Comparison of efficacy of ultrasound-guided pectoral nerve block versus thoracic paravertebral block using levobupivacaine and dexamethasone for postoperative analgesia after modified radical mastectomy: A randomized controlled trial - Ashwini Siddeshwara; Geeta Singariya; Manoj Kamal; Kamlesh Kumari; Satyanarayan Seervi; Rakesh Kumar (Saudi Journal of Anaesthesia, 2019)
Background and Aims: Pectoral nerve (PecS II) block is the latest modality for providing postoperative analgesia after breast surgery. The present study was planned to compare the analgesic efficacy of thoracic paravertebral block (TPVB) and PecS II for postoperative analgesia after modified radical mastectomy (MRM). Methods: A total of 40 female patients undergoing radical mastectomy were randomly allocated into two groups (n = 20). Group T received ultrasound-guided TPVB, while group P received PecS II block using 0.25% levobupivacaine 24 ml + dexamethasone 1 ml (4 mg) before induction of anesthesia. The primary outcome was duration of analgesia (time to request first analgesic dose), while total rescue analgesic consumption in first 24 h, numeric rating score (NRS), and complication were secondary outcomes. The data were analyzed using IBM SPSS software version 22.0. Results: The duration of analgesia was significantly prolonged in the group P than group T (474.1 ± 84.93 versus 371.5 ± 51.53 min, respectively; P < 0.0001). Postoperative morphine consumed at 24 h was less in the group P than group T (11.25 ± 4.75 and 15.0 ± 4.86 mg, respectively; P = 0.018). NRS at movement and rest were lower in the group P as compared to group T at all time intervals (median 3 versus 4). No block-related complication was recorded in any group. Conclusions: The 0.25% levobupivacaine with dexamethasone 4 mg in PecS II block provided longer duration of analgesia than the TPVB in patients undergoing MRM without any adverse effects.